2020
DOI: 10.1113/jp280405
|View full text |Cite
|
Sign up to set email alerts
|

The microRNA miR‐133b functions to slow Duchenne muscular dystrophy pathogenesis

Abstract: Impairment of muscle biogenesis contributes to the progression of Duchenne muscular dystrophy (DMD). r As a muscle enriched microRNA that has been implicated in muscle biogenesis, the role of miR-133b in DMD remains unknown. r To assess miR-133b function in DMD-affected skeletal muscles, we genetically ablated miR-133b in the mdx mouse model of DMD. r We show that deletion of miR-133b exacerbates the dystrophic phenotype of DMD-afflicted skeletal muscle by dysregulating muscle stem cells involved in muscle bio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 78 publications
(195 reference statements)
2
14
0
1
Order By: Relevance
“…Using AAV-mediated expression of Cre-recombinase to temporally knockdown Ago2 in skeletal muscles of juvenile mice, we found that reduced levels of Ago2 caused an increased presence of thickened interstitial space, moderately altered the morphology of AChR clusters, but did not impact the size of muscle fibers or their NMJ endplates. The absence of an overtly deleterious phenotype following Ago2 knockdown is in line with previous studies that found that otherwise healthy skeletal muscles are minimally impacted by deletion of individual miRNAs 13 , 35 , 36 . For example, global deletion of miR-133b did not produce an observable effect on the health of juvenile or adult skeletal muscle fibers, their NMJs or their transcriptome 36 .…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Using AAV-mediated expression of Cre-recombinase to temporally knockdown Ago2 in skeletal muscles of juvenile mice, we found that reduced levels of Ago2 caused an increased presence of thickened interstitial space, moderately altered the morphology of AChR clusters, but did not impact the size of muscle fibers or their NMJ endplates. The absence of an overtly deleterious phenotype following Ago2 knockdown is in line with previous studies that found that otherwise healthy skeletal muscles are minimally impacted by deletion of individual miRNAs 13 , 35 , 36 . For example, global deletion of miR-133b did not produce an observable effect on the health of juvenile or adult skeletal muscle fibers, their NMJs or their transcriptome 36 .…”
Section: Discussionsupporting
confidence: 89%
“…The absence of an overtly deleterious phenotype following Ago2 knockdown is in line with previous studies that found that otherwise healthy skeletal muscles are minimally impacted by deletion of individual miRNAs 13 , 35 , 36 . For example, global deletion of miR-133b did not produce an observable effect on the health of juvenile or adult skeletal muscle fibers, their NMJs or their transcriptome 36 . By contrast, deletion of miR-133b in the mdx mouse model of Duchenne muscular dystrophy exacerbated dystrophic muscle pathology and induced widespread transcriptomic changes 36 .…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations